Interpretative and constructionist accounts: their usefulness for understanding “social problems” - Jacobs, Keith (SocietàMutamentoPolitica, 2018)
Whilst there are very few academics who would advocate a wholly positivist approach to the study of social problems, there is a tendency to valorise supposedly objective, quantitative studies in the field of social policy. This tendency has been reinforced by government’s demand for research that provides ‘evidence’. Briefly stated, governments now encourage researchers to identify causal components underpinning problems such as homelessness and then make policy recommendations to ameliorate them. In this paper I consider the merits of the contribution of constructionist perspectives for social policy research that challenge hegemonic understandings of social problems. I begin by tracing some of the influential critiques that emerged from the 1970s onwards including symbolic interactionism, Foucauldian inspired discourse analysis, constructionism and more recently actor network theory. The main part of the paper provides an assessment of these approaches with reference to UK housing policy, noting both their limitations and strengths. Finally, the paper considers the future tasks for critically orientated social policy scholarship at a time of increasing austerity and social polarisation. Can constructionist and other interpretative accounts provide insights for understanding the failures that beset contemporary policy making in areas such as housing?